Investigation of the physiological and molecular regulatory mechanism of soluble sugar metabolism in Lavandula angustifolia Mill. under cold stress - Liang, Yuchen; Liu, Yinan; Wang, Yu; Yang, Ruijiao; Yuan, Zening; Li, Hui (Frontiers in Plant Science, 2025)
Lavender (Lavandula angustifolia Mill.) is a valuable aromatic plant with significant commercial importance. However, cold stress–one of the primary abiotic factors impacting sugar metabolism–adversely affects its agricultural productivity in Northeast China. To investigate the mechanisms underlying cold tolerance in L. angustifolia and support economic development, we measured the sugar content and performed transcriptome analysis at temperatures of 30°C (control), 20°C, 10°C, and 0°C. The results revealed that when the temperature dropped from 30°C to 0°C, the amylase activities and the content of maltose and glucose increased, while the starch content decreased. During the process, the up-regulation of LaAMY and LaBAM1/3 suggests an adaptive response in L. angustifolia to cold stress by promoting the breakdown of starch. Meanwhile, the up-regulation of sugar metabolism genes LaRHM1, LaMUR4, LaUGD4, alongside the downregulation of photosynthesis-related genes LaPSAD1, LaPSAN, LaPSBQ2, LaLHCB4.2, and LaPSB27-1 illustrate a strong connection to soluble sugar metabolism. These key genes exhibit significant correlations with starch content and amylase activities, specifically in the decomposition of starch into soluble sugars. The results indicate the decomposition of starch into soluble sugars plays a crucial role in osmotic regulation, facilitating subsequent sugar metabolism in L. angustifolia under cold stress. The correlation between gene expression and physiological indicators suggests that genes can potentially mitigate light-induced damage while promoting cellular homeostasis. Molecular docking analyses between the proteins PSAN and RHM1, MUR4 and UGD4, as well as between LHCB4.2 and RHM1, MUR4, and UGD4 predict that these protein interactions involved in sugar metabolism and photosynthesis contribute to enhancing cold resistance in L. angustifolia.